Problems and obstacles in using Information and Communication Technology (ICT) among Malaysian agro-based entrepreneurs - Hassan, Md. Salleh; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva (EuroJournals Publishing, 2009)
The main objectives of this paper is to discover the main problems faced by Malaysian agro-based entreprenuers and factors that affect it. A total of 450 respondents were selected from all states in Peninsular Malaysia respresenting six types of agro-based industry namely food processing, non-food processing, farming, animal rearing, fisheries and plantation. Results gained concluded that five main problems faced by the agro-based entreprenuers were they did not know the benefits of ICT, did not have skills or expertise in using ICT , lack of time spent on ICT , difficulties in using ICT and did not have ICT knowledge . Chi-square test done proved that the factor of education achievement has significant difference with all the five main problems while age was found to have significant difference with only two of the five main problems.